Does military draft discourage enrollment in higher education? : evidence from OECD countries - Katarina Keller; Panu Poutvaara; Andreas Wagener (Center for Economic Studies and ifo Institute (CESifo), 2009)
Using data from 1960-2000 for OECD countries, we analyze the impact of compulsory military service on the demand for higher education, measured by students enrolled in tertiary education as a share of the working-age population. Based on a theoretical model, we hypothesize that military draft has a negative effect on education. Empirically, we confirm this for the existence of conscription, albeit usually at low statistical significance. However, the intensity of its enforcement, measured by the share of the labor force conscripted by the military and the duration of service, significantly reduces enrollment in higher education.
Keywords: H56; I20; 330; conscription; human capital; Wehrdienst; Humankapital; Studium; OECD-Staaten